A temperature‐compensated linear GaAs HBT power amplifier for small‐cell applications in −25 to 125∘C$^° \rm C$ lunar environment. Issue 18 (15th July 2022) - Li, Jiajin; Zhang, Gary; Yang, Chang
Abstract: A two‐stage 920–960 MHz power amplifier (PA) in GaAs heterojunction bipolar transistor (HBT) process is demonstrated for small‐cell communications in the lunar environment. To cope with the temperature fluctuations during lunar days, a novel complementary to absolute temperature (CTAT) biasing scheme is proposed for the PA to achieve an ultra‐wide‐range temperature compensation. Moreover, to meet the linearity requirements of the small‐cell applications while producing high output power, a band‐stop filter is employed in the biasing circuit of the second stage to reduce the AM– AM distortions. Over the temperature range of −25 to 125°C, the PA is capable of operating for the small‐cell applications over a gain ranging from 30.2 to 32.8 dB. The proposed PA achieves 24.5 dBm linear power with −47 dBc adjacent channel leakage ratio (ACLR) and a PAE of 15%.